Solve for x 6x - 76 = 2
You're trying to get x by itself. So we start by adding 76 to both sides to get it away from the x 6x - 76 + 76 = 2 + 76 6x = 78 Now we divide both sides by 6 6x/6 = 78/6 which gives us x = 13
Simplify 7(6x - (3 - 6y + 2x) + 4y)
You start by performing the operations in the parenthesis 7(6x - (3 - 6y + 2x) + 4y) Since none of the terms are the same in the middle parenthesis we can just drop the parenthesis and change the signs accordingly to the sign in front of the parenthesis. Since it is a negative we'll multiply those three terms by negative one. 7(6x - 3 + 6y - 2x +4y) Now we want to combine any like terms in the parenthesis 7( 4x - 3 + 10y) Now that everything that can be combined is, we can multiply everything in the parenthesis by the number on the outside, which is 7. 28x -21 +70y This is our final answer because there is no more like terms to combine.
Solve for x in the following equation: l 2x-1 l = l 4x+3 l
When solving absolute values there is two different ways the problem can be written out. 2x - 1 = 4x + 3 or 2x - 1 = - (4x + 3) You have to solve for both equations 2x - 1 = 4x + 3 You start by getting all of your x's on one side 2x -2x - 1 = 4x -2x + 3 -1 = 2x + 3 Then you want to get all of your other numbers on the other side of the equation. -1 - 3 = 2x + 3 - 3 -4 = 2x Now you can divide each side by 2 in order to get x by itself -4/2 = 2x/2 -2 = x Now we need to solve for the other equation 2x - 1 = -(4x + 3) We can start by multiplying whats in the parenthesis by the negative one on the outside of it. 2x - 1 = -4x - 3 Now lets get all of our x's on one side and our other numbers on the other side. 2x + 4x - 1 = -4x +4x -3 6x - 1 = -3 6x - 1 + 1 = -3 + 1 6x = -2 Divide both sides by 6 6x/6 = -2/6 x = -2/6 Simplify the fraction to lowest terms x = -1/3 So now we know that x can be either -2 or -1/3